Drama in Education and Its Influence on Adolescents’ Empathy - George Mardas; Kostas Magos (Randwick International of Education and Linguistics Science Journal, 2020)
Drama in education can trigger feelings and provoke thoughts in the school classroom. Children are invited to use their minds and senses and get in touch with their emotions. The participants, who get engaged in such an endeavour, undergo a transformation by impersonating different characters, fictional or real-life and come up with a variety of solutions to problems in a fictional framework. Through this process the students’ empathy could be developed. The present case study using qualitative research techniques analyzes the outcome of a practical implementation through drama in a Greek Secondary School. The main research question was whether and to what extent educational drama can influence in a positive way middle adolescents’ empathy. The research findings showed that the use of drama supported the participants to realize the importance of a specific social situation, and helped them grasp the difference between cognitive and emotional empathy.